Circadian Rhythms in the CNS and Peripheral Clock Disorders: Role of the Biological Clock in Cardiovascular Diseases - Koji Maemura; Norihiko Takeda; Ryozo Nagai (Elsevier, 2007)
The cardiovascular diseases are closely related to circadian rhythm, which is under the control of the biological clock. Clock genes show circadian oscillation not only in the suprachiasmatic nucleus but also in peripheral tissues, suggesting the existence of the peripheral clock. We previously demonstrated that plasminogen activator inhibitor-1 (PAI-1) might be an output gene of the peripheral clock. To further elucidate the functional relevance of the peripheral clock in the cardiovascular system, we screened target genes of the peripheral clock by cDNA microarray analysis. A total of 29 genes including transcription factor, growth factors, and membrane receptors were upregulated by CLOCK/BMAL and showed circadian oscillation. These results suggest that cardiovascular systems have their own peripheral clocks, and at least in part, they may regulate the circadian oscillation of cardiovascular function directly. These results potentially provide a molecular basis for the circadian variation of cardiovascular function and novel strategies for the prevention and treatment of cardiovascular diseases. Keywords:: cardiovascular, peripheral clock, circadian rhythm